Daily and annual cycles in thermoregulatory behaviour and cardio-respiratory physiology of black and white tegu lizards - Sanders, Colin E.; Tattersall, Glenn J.; Reichert, Michelle; Andrade, Denis V. [UNESP]; Abe, Augusto S. [UNESP]; Milsom, William K. (Springer, 2015)
This study was designed to determine the manner in which metabolism is suppressed during dormancy in black and white tegu lizards (Tupinambis merianae). To this end, heart rate (f (H)), respiration rate (f (R)), and deep body temperature (T (b)) were continuously monitored in outdoor enclosures by radio-telemetry for nine months. There was a continuous decline in nighttime breathing and heart rate, at constant T (b), throughout the late summer and fall suggestive of an active metabolic suppression that developed progressively at night preceding the entrance into dormancy. During the day, however, the tegus still emerged to bask. In May, when the tegus made a behavioural commitment to dormancy, T (b) (day and night) fell to match burrow temperature, accompanied by a further reduction in f (H) and f (R). Tegus, under the conditions of this study, did arouse periodically during dormancy. There was a complex interplay between changes in f (H) and T (b) associated with the direct effects of temperature and the indirect effects of thermoregulation, activity, and changes in metabolism. This interplay gave rise to a daily hysteresis in the f (H)/T (b) relationship reflective of the physiological changes associated with warming and cooling as preferred T (b) alternated between daytime and nighttime levels. The shape of the hysteresis curve varied with season along with changes in metabolic state and daytime and nighttime body temperature preferences.
Keywords: Reptiles; Tegu lizards; Torpor; Dormancy; Hibernation; Cardiorespiratory control; Seasonal adjustments